2006
DOI: 10.1523/jneurosci.4265-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Changes in the Noradrenergic Nervous System in the Locus Ceruleus and Hippocampus of Postmortem Subjects with Alzheimer's Disease and Dementia with Lewy Bodies

Abstract: In Alzheimer's disease (AD), there is a significant loss of locus ceruleus (LC) noradrenergic neurons. However, functional and anatomical evidence indicates that the remaining noradrenergic neurons may be compensating for the loss. Because the noradrenergic system plays an important role in learning and memory, it is important to determine whether compensation occurs in noradrenergic neurons in the LC and hippocampus of subjects with AD or a related dementing disorder, dementia with Lewy bodies (DLB). We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
244
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(269 citation statements)
references
References 65 publications
23
244
2
Order By: Relevance
“…Having demonstrated in the present study that oxygenation patterns, as observed in sleep apnea, can significantly injure the locus ceruleus, it will be of interest to look for disease interactions between obstructive sleep apnea (present in Ͼ10% of elderly humans) and Alzheimer's disease. In Alzheimer's disease, locus ceruleus loss may be accompanied by compensatory changes, including dendritic and axonal sprouting (Szot et al, 2006). In the present model of hypoxia/reoxygenation injury, neuronal compensation is not evident, because dendrites are substantially reduced and many remaining dendrites show vacuolization.…”
mentioning
confidence: 67%
“…Having demonstrated in the present study that oxygenation patterns, as observed in sleep apnea, can significantly injure the locus ceruleus, it will be of interest to look for disease interactions between obstructive sleep apnea (present in Ͼ10% of elderly humans) and Alzheimer's disease. In Alzheimer's disease, locus ceruleus loss may be accompanied by compensatory changes, including dendritic and axonal sprouting (Szot et al, 2006). In the present model of hypoxia/reoxygenation injury, neuronal compensation is not evident, because dendrites are substantially reduced and many remaining dendrites show vacuolization.…”
mentioning
confidence: 67%
“…Importantly, the loss of LC neurons was found to be more extensive and to correlate better with the progression of AD than the cholinergic cell loss observed in the nucleus basalis of Meynert (15,16). In contrast, compensatory mechanisms regarding NE levels in the CSF and the mRNA expression of α2-adrenoreceptors in the hippocampus of AD patients have been suggested (17)(18)(19). However, it is unclear whether increased NE measured form the CSF is congruent with the NE secreted from LC projection areas, but being produced in the brainstem or by terminally degenerated LC neurons.…”
Section: Ne Depletion Decreases Microglial Phagocytosis and Recruitmementioning
confidence: 98%
“…)), thus indicating that cell shape/size were not confounding the cell counts. Because different portions of the LC innervate different structures (Szot et al, 2006), sections were systematically taken to include the 30, 50, and 70% levels of the LC (Fig. 6d).…”
Section: Increase In the Number Of Noradrenergic Neurons In Tgntrk3mentioning
confidence: 99%